Depor newspaper front pages (Torneo Liga 1 - 2022, Apertura stage): a semiotic perspective - Castro, Carmen (2023)
This article analyzes the soccer sports front pages issued by the newspaper Depor during the Liga 1-2022 tournament, Apertura stage. Based on Peirce's (1986) semiotic approaches on the sign, a set of signs organized in a larger unit called news sign unit is identified, which is explained according to Barthes' (2000) foundations, related to the denotative and connotative sense that every sign enjoys. The research concludes that this news sign unit has a deliberate composition, a defined communicative objective and is a semiological system or myth, in the sense that it expresses the collective representation of the reality of a certain social group or community: the soccer sports community.